Social Responsibility Concerns of SMEs in Romania, from the Perspective of the Requirements of the EFQM European Excellence Model - Marieta Olaru; Ghiorghiţa Stoleriu; Ioana Maria Diana Şandru (Amfiteatru Economic Journal, 2011)
The paper highlights some of the results obtained within a questionnaire-based survey conducted in the SMEs from Romania, the objectives being measurement of the degree to which these enterprises fulfil the EFQM (European Foundation for Quality Management) requirements regarding the social responsibility and measurement of the impact that the implementation of a quality management system according to the ISO 9001 standard has on the degree of fulfilment of these requirements. The research was carried out on a representative sample of SMEs from Romania, in the period 2007-2010, with data being processed from 918 filled-in questionnaires. The results of the research show that SMEs in Romania are especially concerned with reducing and preventing health and occupational safety risk. In contrast, SMEs are less concerned with: the active involvement in the community life, the assessment of the community's perception on the organization's social impact and the use of performance indicators related to this impact. However, it was confirmed that the implementation of a quality management system according to the ISO 9001 standard had a positive impact on the ability of SMEs in Romania to fulfil the requirements of the EFQM Excellence Model related to social responsibility. This work received support from CNCSIS –UEFISCSU, through the ID_856 PNII – IDEI research project, code 273//2007.
Keywords: M14; 330; social responsibility; the EFQM Excellence Model; quality management system; SMEs